Improving fuel economy through changes in engine and transmission design. (5th August 2014) - Mitschke, M.
Engine design, transmission design, tractive resistance and driving style all have considerable influence on fuel economy. This paper discusses the influences of the various quantities. Considerable savings in fuel consumption can be achieved either by using a continuously variable transmission which permits current engines to run in their optimum operating condition, or by an engine for which conditions of constant fuel consumption coincide with conditions of constant power. In this case conventional gearboxes will be sufficient.